Koeksistensi alam dan budaya dalam arsitektur - Tarcicius Yoyok Wahyu Subroto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
The existence of residential buildings scattered across the archipelago that has been present for centuries and leaves a long footprint both culturally and socially and integrated into the lives of those who have it has a wealth of extraordinary values ​​of local wisdom. This reality leads to the logical awareness of researchers and observers about the relationship of the concepts of culture and material culture that are not only to be studied and expressed textually but also important to be documented to add to the wealth of information and documentation of culture and architecture. assets that will ultimately contribute to its main mission of developing architectural science. Subroto (2008) states that basically science is used to explain the basic principles contained in knowledge that were previously known as important elements of science itself.